FENOMENA GLOBAL SHIFTING DAN PENGARUHNYA TERHADAP PERKEMBANGAN E-COMMERCE DI INDONESIA - Melaty Anggraini (Jurnal Paradigma, 2021)
Globalization has been general nowadays. Usually, it defined as a process of effect diffusion in economy, social and culture. In economic perspective, globalization being considered to convey interdepedence and competition to each others. Meanwhile, international relations study view these phenomenon as kind of instrument of global shifting. These include shifting in regimes, power and market structure of political economy dynamic which integrated by the rapid technological advancement. As the part of international structure, Indonesia got involved through the rise and development of e-commerce. Therefore, this paper aimed to review those phenomenon thorugh some questions. This paper then found that global shifting in international economy frame encourage the development of e-commerce, which is a new model of economic activity. These trend also developed rapidly in Indonesia signed by the emergence of economic platform and of course, influenced to economic dynamic in Indonesia.